2008
DOI: 10.1053/j.ajkd.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Patients' Reports of Comorbid Disease and Their Association With Mortality in ESRD

Abstract: Background-Patient awareness of chronic diseases is low. Unawareness may represent poor understanding of chronic illness and may be associated with poor outcomes in end-stage renal disease (ESRD) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 32 publications
2
26
0
1
Order By: Relevance
“…Among the limitations of our study is that history of diabetes was self-reported. However, diabetes is a serious chronic condition and it has been reliably recalled in other epidemiological studies [49,50]. Furthermore, it is possible that self-reported information on medical conditions is reported more accurately in cases than in population-controls, but not necessarily in hospital-controls [49].…”
Section: Discussionmentioning
confidence: 99%
“…Among the limitations of our study is that history of diabetes was self-reported. However, diabetes is a serious chronic condition and it has been reliably recalled in other epidemiological studies [49,50]. Furthermore, it is possible that self-reported information on medical conditions is reported more accurately in cases than in population-controls, but not necessarily in hospital-controls [49].…”
Section: Discussionmentioning
confidence: 99%
“…There was strong evidence supporting the reliability and validity of self-reported diabetes mellitus, where agreement between self-reported disease diagnosis and medical conditions was observed. 5557 In addition, several studies reported high correlations between recalled and measured weight and height in young adulthood among middle-aged and older men and women. 5862 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the published literature (2), patients with diabetes mellitus and patients with nasal carriage of S. aureus upon study entry were at a higher risk of infection. The high prevalence of both risk factors at baseline underscore their importance for patients with ESRD (20,21). This study is also consistent with previous studies showing that patients with synthetic or heterologous tissue grafts are at higher risk of S. aureus infection than patients with arteriovenous fistulas (22).…”
Section: Discussionmentioning
confidence: 99%